2007
DOI: 10.1093/bioinformatics/btm389
|View full text |Cite
|
Sign up to set email alerts
|

DNA reference alignment benchmarks based on tertiary structure of encoded proteins

Abstract: This work presents the first known multiple DNA sequence alignment benchmarks that are (1) comprised of protein-coding portions of DNA (2) based on biological features such as the tertiary structure of encoded proteins. These reference DNA databases contain a total of 3545 alignments, comprising of 68 581 sequences. Two versions of the database are available: mdsa_100s and mdsa_all. The mdsa_100s version contains the alignments of the data sets that TBLASTN found 100% sequence identity for each sequence. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…MAFFT with the L-INS-i option has shown to be the most accurate and consistent method for the alignment of sequences (Wilm et al 2006;Carroll et al 2007). The alignment of 558 bp from cytochrome oxidase I (mt-COI) was analysed under several optimality criteria: (1) Parsimony using PAUP* 4.0b10 (Swofford 2001) to build tree(s) with TBR branch swapping and 10,000 random additions saving all most parsimonious trees, (2) Bayesian inference using the computer program MrBayes v3.1.2 (Huelsenbeck and Ronquist 2001;Ronquist and Huelsenbeck 2003) with the GTR ?…”
Section: Phylogenetic Reconstructionmentioning
confidence: 99%
“…MAFFT with the L-INS-i option has shown to be the most accurate and consistent method for the alignment of sequences (Wilm et al 2006;Carroll et al 2007). The alignment of 558 bp from cytochrome oxidase I (mt-COI) was analysed under several optimality criteria: (1) Parsimony using PAUP* 4.0b10 (Swofford 2001) to build tree(s) with TBR branch swapping and 10,000 random additions saving all most parsimonious trees, (2) Bayesian inference using the computer program MrBayes v3.1.2 (Huelsenbeck and Ronquist 2001;Ronquist and Huelsenbeck 2003) with the GTR ?…”
Section: Phylogenetic Reconstructionmentioning
confidence: 99%
“…This algorithm correctness is verified by aligning two sequences from BAliBASE DNA sequence alignment benchmark [18]. These sequences are Saccharomyces cereviseae GlyRS1 (SYG_YEAST) and Schizosaccharomyces pombe GlyRS (SYG_SCHPO).…”
Section: A-tgamentioning
confidence: 99%
“…The best known of these benchmark datasets is probably BAliBASE [94], but others are also used [95][96][97][98]. The choice of benchmarks and how they are used has a large impact on the result of the evaluation, and so has been discussed in several papers [24,78,[99][100][101].…”
Section: Benchmark Datasetsmentioning
confidence: 99%
“…The use of treelength optimization to find good trees (and/or alignments) is a matter of substantial controversy in phylogenetics [98,102,227,248,[258][259][260][261]. Most of the studies that have examined the accuracy of POY trees and alignments explored performance under simple gap penalties, and found that POY did not produce trees and alignments of comparable accuracy to maximum parsimony on the ClustalW alignment, denoted MP(Clustal) [259,262].…”
Section: Poymentioning
confidence: 99%